1994
DOI: 10.2307/1131380
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, Teacher, and Child Care History Correlates of Children's Relationships with Peers

Abstract: Mother and teacher correlates of social competence with familiar and unfamiliar peers in 84 children who entered child care at three different times are examined. Social competence at age 4 was assessed with both familiar and unfamiliar peers. Relationships with both initial and 4-year-old teachers were related to social competence with peers. Maternal attachment relationships at 12 months and at 4 years did not predict social competence with peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1
11

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(99 citation statements)
references
References 0 publications
5
82
1
11
Order By: Relevance
“…This is consistent with previous studies, suggesting the quality of children's relationship with their mothers was unrelated to prosocial behavior, when the effect of the teacher-child relationship is considered (Howes et al, 1994;Kienbaum et al, 2001;Mitchell-Copeland et al, 1997). In these previous studies, the absence of associations between the mother-child relationship and children's prosocial behavior was attributed to a context effect (Howes et al, 1994;Kienbaum et al, 2001;Mitchell-Copeland et al, 1997). As in previous studies, the current study failed to confirm a direct association between the mother-child relationship and children's prosocial behavior.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with previous studies, suggesting the quality of children's relationship with their mothers was unrelated to prosocial behavior, when the effect of the teacher-child relationship is considered (Howes et al, 1994;Kienbaum et al, 2001;Mitchell-Copeland et al, 1997). In these previous studies, the absence of associations between the mother-child relationship and children's prosocial behavior was attributed to a context effect (Howes et al, 1994;Kienbaum et al, 2001;Mitchell-Copeland et al, 1997). As in previous studies, the current study failed to confirm a direct association between the mother-child relationship and children's prosocial behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Even though our findings showed the teacher-child relationship to be significantly associated with children's prosocial behavior, the association between mother-child relationships and children's prosocial behavior was non-significant. This is consistent with previous studies, suggesting the quality of children's relationship with their mothers was unrelated to prosocial behavior, when the effect of the teacher-child relationship is considered (Howes et al, 1994;Kienbaum et al, 2001;Mitchell-Copeland et al, 1997). In these previous studies, the absence of associations between the mother-child relationship and children's prosocial behavior was attributed to a context effect (Howes et al, 1994;Kienbaum et al, 2001;Mitchell-Copeland et al, 1997).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Howes (1999) suggested that more than one caregiver may be able to assume the role of attachment figures for a child. Studies by Howes et al indicated that a secure attachment relationship with a professional caregiver compensated an insecure attachment relationship with the mother (Howes, Rodning, Galuzzo, & Myers, 1998) and security of attachment to the babysitter was more effective than child-mother attachment security in predicting the child's social competence (Howes, Matheson, & Hamilton, 1994). Barnas and Cummings (1994) found in their study that children were able to form attachment to caregivers who provide them regular care.…”
Section: Resultsmentioning
confidence: 99%